Bimetallic Ru-Sn as Effective Catalysts for the Selective Hydrogenation of Biogenic Platform Chemicals at Room Temperature - Azzahra, Atina Sabila; Dewi, Heny Puspita; Mikrianto, Edi; Sembiring, Kiky Corneliasari; Sunnardianto, Gagus Ketut; Nata, Iryanti Fatyasari; Rodiansono, Rodiansono; Jayanudin, Jayanudin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Supported bimetallic ruthenium-tin (denoted as Ru-Sn(x); x = molar ratio of Ru/Sn) catalysts were examined for room temperature (RT) hydrogenation of biogenic platform chemicals of levulinic acid (LA) to g-valerolactone (GVL). Six types of metal oxide support c.a. Nb2O5, TiO2, ZnO, ZrO2, g-Al2O3, active charcoal (AC), were employed as the support for Ru-Sn(x). Ru-Sn(3.0)/Nb2O5 (Ru/Sn = 3.0) that reduced at 500 oC demonstrated the highest yield of GVL (98%) at 30 oC, 30 bar H2 for 3 h. The increase in Sn loading amount (Ru/Sn = 1.5) resulted in decreasing of LA conversion (83%) under the same reaction conditions. Among the studied supported Ru-Sn catalysts, Nb2O5 and ZnO supports exhibited better catalytic performances than that other for RT hydrogenation of LA and various biogenic platform chemicals. The Ru-Sn(3.0)/Nb2O5 catalyst was characterized by means of various adsorption and spectroscopic techniques. The Ru-Sn(3.0)/Nb2O5 catalyst was found to be reusable without any significant loss of its activity. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).